Primary Congenital Glaucoma presenting with Acute Corneal Hydrops: a challenging approach to amblyopia prevention - Rita Rodrigues; João Pinheiro-Costa; Joana Araújo; António Benevides Melo; Augusto Magalhães; Sérgio Estrela-Silva (Case Reports in Ophthalmology)
Introduction: Acute hydrops is a rare initial manifestation of Primary Congenital Glaucoma (PCG). It can result in significant corneal opacity, posing an additional risk for amblyopia development in PCG patients. We report a case of a newborn with PCG presenting with acute corneal hydrops and significant corneal scarring, discussing the management and challenges of amblyopia prevention. Case Presentation: A 3-day-old female newborn was referred to our department due to bilateral corneal clouding. Anterior segment examination revealed bilateral corneal edema, with severe corneal prolapse in the right eye consistent with acute hydrops. The anterior chamber structures of the right eye were indiscernible due to significant corneal edema. The left eye presented a deep, quiet anterior chamber with no dysgenesis of anterior segment structures. Intraocular pressure (IOP) measurements were >40 mmHg in both eyes. Corneal diameters were 10 mm OD and 12 mm OS. Fundoscopic posterior segment assessment was not possible due to unclear media. B-scan ultrasonography revealed no significant changes. The patient underwent urgent bilateral trabeculotomy. Postoperatively, intense mechanical stretching induced by severely increased IOP was visible, with the right cornea exhibiting a central opacity managed with topical corticosteroids and showing improvement. Right corneal opacity spared the superior cornea, and atropine drops combined with left eye occlusion were employed to mitigate right eye deprivation amblyopia. Eighteen months later, the patient can fixate and follow objects with the right eye. Left eye corneal transparency was restored, and bilateral IOP control was achieved. Conclusion: Despite prompt surgical treatment, acute hydrops presents a postoperative management challenge and may result in irreversible corneal scarring. Timely management of corneal opacities is crucial to prevent amblyopia. A multidisciplinary approach is essential for the best visual outcome.